In-vitro evaluation of porcupine bezoar extracts (PBE) as anti-cancer agent on HeLa cell line – A preliminary study - Azizulkarim, Azra Hazwanie; Abdul Jamil, Muhammad Mahadi; Adon, Mohamad Nazib; Abdul Wahab, Ridhwan; Tengku Ibrahim, Tengku Nadzlin; Hamdan, Salehhuddin; Baba, Sayang (AIP Publishing, 2018)
Porcupine Bezoar Extract (PBE) has been previously described to possess diverse medicinal properties. In any case, its potential and ability as anti-cancer agent on HeLa cell line are still poorly studied and understood. Hence, in this research, Porcupine Bezoar Extract (PBE) aqueous extract was figure out for its potential as a safe anti-cancer agent. Initially, Porcupine Bezoar Extract (PBE) was infused with distilled water for 18 hours to get PBE aqueous solution in order to confirm the presence of bioactive agents as antioxidants. Later, PBE aqueous solution was subjected to HeLa cell line and was observed for 48 hours exposures with comparative to the untreated cell to evaluate its anticancer potential and ability. The data from this study propose the potential agents for improving human health, especially in the anti-cancer application.